LIFE INSURANCE HOLDINGS AND WELL‐BEING OF SURVIVING SPOUSES. (18th November 2016) - Harris, Timothy F.; Yelowitz, Aaron
Abstract : Premature death of a breadwinner can have devastating financial consequences on surviving dependents. This study investigates the role of life insurance in mitigating the long‐run financial consequences of spousal mortality. Using the Health and Retirement Study, we examine individuals whose spouses died during or soon after his or her peak earnings years. After controlling for socioeconomic status, we find that sizable lump‐sum life insurance payouts do not significantly influence spousal well‐being. ( JEL D31, G22, I31, J32, J33, J38)